2003
DOI: 10.1021/la0268810
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Growth of Water-in-CO2 Miniemulsions

Abstract: We report nonflocculated dilute water-in-CO2 (W/C) miniemulsions stable for 24 h in contrast with flocculated unstable macroemulsions reported previously. The surfactants, poly(1,1-dihydroperfluorooctyl methacrylate)-b-poly(ethylene oxide) (PFOMA-b-PEO), were synthesized by atom transfer radical polymerization to achieve the proper hydrophilic-CO2-philic balance (HCB) and a low interfacial tension (∼0.2-2 mN/m) between water and CO2. The average particle diameter, ranging from 70 to 140 nm, was measured with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 61 publications
2
57
0
Order By: Relevance
“…The temperature was controlled to ±0.1 • C by immersing both the view cell and the homogenizer into water baths equipped with temperature controllers (Julabo, Inc.). The morphology of the emulsion was determined via electrical conductivity measurements, as described elsewhere [12].…”
Section: Emulsion Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature was controlled to ±0.1 • C by immersing both the view cell and the homogenizer into water baths equipped with temperature controllers (Julabo, Inc.). The morphology of the emulsion was determined via electrical conductivity measurements, as described elsewhere [12].…”
Section: Emulsion Formationmentioning
confidence: 99%
“…As a result of these beneficial properties, carbon dioxide has emerged as an alternative to traditional organic solvents in the preparation of colloidal dispersions [2][3][4][5][6], including microemulsions [3,[7][8][9], miniemulsions [10][11][12], macroemulsions [13][14][15][16][17][18], and polymer latexes [19,20]. Water-in-CO 2 (W/C) miniemulsions [10,12], with droplets ranging from 50 to 500 nm in diameter, and macroemulsions [14,15,18,21], consisting of droplets greater than 500 nm, are formed by shear and are stabilized kinetically, whereas microemulsions are thermodynamically stable. Examples of applications for these liquid or solid dispersions include dry cleaning [22], photoresist drying [23], metal extraction [24], nanoparticle synthesis [25,26], and enzymatic catalysis [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to investigations of engineering applications utilizing both W/CO 2 microemulsion and macroemulsion, basic studies from the viewpoint of thermodynamic stability and interfacial behavior were reported by Johnston et al [15][16][17][18][19][20][21][22][23]. Moreover, a phase diagram is also important for the development of novel processes utilizing W/CO 2 microemulsion and macroemulsion, therefore, the phase behaviors of the scCO 2 + surfactant + water systems were also measured.…”
Section: Introductionmentioning
confidence: 99%